Analysis of Physical Fitness Activities and Basic Movement Skills in Upper Elementary School Students in Muara Bulian District - Norito, Tri Bayu; Satriawan Chan, A. Apri; Isnanta, Raden (S&Co Publishing, 2025)
This study examines the relationship between physical fitness activities and basic movement skills among upper elementary students in Muara Bulian District. Using a quantitative survey of 200 grade V and VI students, data were collected through questionnaires and observation sheets, then analyzed using descriptive statistics and Pearson correlation via SPSS. Results show students exercised an average of 2.31 times per week, with only 45% routinely active. The average movement skill score was 65.27, with 50% performing well. A significant positive correlation was found between physical activity frequency and movement skills (r = 0.472; p < 0.01). The study highlights the need for better facilities, enhanced PE teacher roles, and parental support to improve physical activity and movement development in schools.Keywords: physical fitness, basic movement skills, elementary school students, physical education, physical activity